Variasi Kadar Filler Pada Campuran Beton Aspal Menggunakan Bahan Tambah Anti Stripping - Wiyono, Eko; Susilowati, Anni (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2019)
Filler function to fill cavities between aggregate granules which can affect the characteristics of asphalt concrete mixture. The purpose of this study is to obtain the characteristics of AC-WC asphalt concrete mixtures and determine the optimum variation of filler content on AC-WC asphalt concrete mixtures using cement fillers and anti-stripping additives that meet the specifications of Bina Marga 2010. ; 5.5%; 6%; 6.5%; 7%; 7.5%; and 8% each made with a variation of cement filler of 1%; 3%; 5%; 7%; and 9%; the addition of Wetfix Be 0.3% to the asphalt. The method of implementation is by mixing the wetfix Be first with asphalt, then aggregating according to the ideal mix gradation proportions. Dependent variables (research parameters) include density, percent cavity in aggregate (VMA), percent cavity filled with asphalt (VFB), percent cavity against mixture (VIM), stability, melt, and results for Marshall (MQ). Marshall testing method based on SNI 06-2489-1991. The results of the study obtained KAO in 1% cement filler variation; 3%; 5%; 7%; and 9%, each at 6.75%; 6.5%; 6.35%; 6.5% and 7.125%. KAO average of 6.65%. The range of cement filler levels which still meet the Marshall parameters at 2% cement filler up to 9%. The optimum cement filler content for asphalt concrete mixture is 5.5%, with a VMA value of 19.19%; VFB 77.12%; VIM 4.39%; Stability of 1670.48kg; melting 4.80mm, and MQ 349.78 kg / mm, meeting the specifications of Bina Marga 2010.